Funerary practices of cremation at the megalithic societies of South-Eastern Iberia: The cemetery of Los Milanes - Paula Becerra Fuello; Gonzalo Aranda Jiménez; Miriam Vílchez Suárez; Sonia Robles Carrasco; Lara Milesi García; Marta Díaz-Zorita Bonilla; Christophe Snoeck; Elisavet Stamataki; Javier Lescure; Margarita Sánchez Romero (PLoS ONE, 2025)
The archaeological excavations undertaken at the Chalcolithic necropolis of Los Milanes have revealed a previously unknown variability in funerary practices in the south-eastern Iberia. For the first time, a megalithic tomb housed a large funerary deposit (28,740 bone fragments) of exclusively cremated human bone remains. For a comprehensive characterization of the funerary ritual, a cutting-edge multi-proxy approach has been undertaken including the osteological study of cremated bone remains, radiocarbon chronology, Fourier-Transform Infrared spectroscopy in Attenuated Total Reflectance mode (FTIR-ATR), and carbon, oxygen and strontium isotope analyses. As a result, the cremation ritual consisted of multi-depositional events of at least 21 individuals chronologically concentrated in the first quarter of the third millennium, principally in the 28th century cal BC. The absence of charcoal/ashes in the funerary chamber and the underrepresentation of anatomical regions such as lower limb and trunk suggest that the cremation took place elsewhere and the bone remains were carefully collected and placed as secondary burial depositions. Different proxies including colour patterns, heat‐induced fractures, the presence of cyanamide in calcined bones would also suggest the cremation of principally complete corpses, burnt soon after death. The ritual of cremation coexisted with inhumations during the third millennium cal BC, suggesting a variability in the body manipulation that previously went unnoticed. Unlike inhumations, through cremation, bodies would have been reduced until being indistinguishable, transforming radically the nature of human beings and their ontological status.